Porphyrin‐Based Metal–Organic Frameworks for Neuromorphic Electronics. Issue 2 (15th February 2023) - Ding, Guanglong; Han, Su-Ting; Kuo, Chi-Ching; Roy, Vellaisamy A. L.; Zhou, Ye
Abstract : Metal‐Organic Frameworks In article number 2200150, Ye Zhou and co‐workers summarize the current progress of porphyrin‐based metal–organic frameworks film preparation methods and the application advances in neuromorphic devices, perform comparative analysis in detail, and put forward the challenges and future research directions.